A 30% incidence of renal cysts with varying sizes and densities in biomedical research swine is not associated with renal dysfunction. Issue 3 (10th September 2020) - Gómez, Belinda I.; Little, Joshua S.; Leon, Alisa J.; Stewart, Ian J.; Burmeister, David M.
Abstract: Background: Renal cystic disease arising from various etiologies results in fluid‐filled cavities within the kidneys. Moreover, preexisting renal dysfunction has been shown to exacerbate multiple pathologies. While swine bred for biomedical research are often clinically inspected for illness/parasites, more advanced diagnostics may aid in uncovering underlying renal abnormalities. Methods: Computed tomography was performed in 54 female prepubertal Yorkshire swine to characterize renal cysts; urine and blood chemistry, and histology of cysts were also performed. Results: Digital reconstruction of right and left kidneys demonstrated that roughly one‐third of the animals (17/54; 31%) had one or more renal cyst. Circulating biomarkers of renal function were not different between animals that had cysts and those that did not. Alternatively, urinary glucose ( P = .03) was higher and sodium ( P = .07) tended to be lower in animals with cysts compared to animals without, with no differences in protein ( P = .14) or potassium ( P = .20). Aspiration of cystic fluid was feasible in two animals, which revealed that the cystic fluid urea nitrogen (97.6 ± 28.7 vs 911.3 ± 468.2 mg/dL), potassium (29.8 ± 14.4 vs 148.2 ± 24.85 mmol/L), uric acid (2.55 ± 1.35 vs 11.4 ± 5.65 mg/dL), and creatinine (60.34 ± 17.26 vs 268.99 ± 95.79 mg/dL) were much lower than in the urine. Histology demonstrated a cyst that markedly compresses the adjacent cortex and is lined by a single layer of flattened epithelium, bounded by fibrous connective tissue which extends into the parenchyma. There is tubular atrophy and loss in these areas. Conclusion: This study provides valuable insight for future studies focusing on kidney function in swine bred for biomedical research.